Transcriptome Analysis Reveals New Insight of Fowl Adenovirus Serotype 4 Infection - Chen, Yuan; Huang, Ruiling; Qu, Guishu; Peng, Yaoshun; Xu, Lihui; Wang, Changkang; Huang, Cuiqin; Wang, Quanxi (Frontiers in Microbiology, 2020)
Since 2015, Fowl adenovirus serotype 4 (FAdV-4) infection has caused serious economic losses to the poultry industry worldwide. We isolated and identified the FAdV-4 strain NP, from infected chickens on a layer farm, using chicken embryo allantoic cavity inoculation, electron microscopy, viral genome sequencing, and regression analysis. To explore the pathogenesis of FAdV-4 infection, we conducted transcriptome sequencing analysis of the liver in chickens infected with FAdV-4, using the Illumina® HiSeq 2000 system. Two days after infection with the FAdV-4 NP strain, 13,576 differentially expressed genes (DEGs) were screened in the liver, among which, 7,480 were up-regulated and 6,096 were down-regulated. Gene ontology (GO) analysis indicated that these genes were involved in 52 biological functions. Furthermore, Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed that those DEGs were involved in 33 pathways. We then focused on the KEGG pathway of phagosome and found that mRNA levels of the twenty-five DEGs in that pathway were up-regulated, and seven DEGs were down-regulated. Real-time quantitative polymerase chain reaction (qPCR) confirmed the accuracy and reliability of these findings. Moreover, 24 h after LMH cells were infected with FAdV-4, the mRNA levels of F-actin, Rab7, TUBA, and DVnein were significantly increased. These four genes were all subsequently silenced by RNA interference, and viral replication of FAdV-4 was then significantly down-regulated. These findings demonstrate the isolation and identification of the FAdV-4 NP strain, and the DEGs in KEGG pathway of phagosome were utilized by FAdV-4 to benefit its infection.